The Proactive Role of Therapeutic Communication in Maintaining Public Mental Health Ahead of 2024 - widi sawitri (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2024)
This research aims to determine the proactive role of therapeutic communication in maintaining people's mental health by 2024. This research is descriptive qualitative, with a literature review research method. The results of this research are that effective and proactive therapeutic communication can help individuals and communities understand, overcome and support mental health. Mental health practitioners who use proactive therapeutic communication can play an important role in providing the support, education, and interventions needed to improve the mental health of society as a whole. With the proactive role of therapeutic communication, mental health practitioners can act as facilitators, supporters, and active sources of information in treating the mental health of individuals or communities